Impact of cysteine mutations on the structural dynamics and functional impairment of SOD1: insights into the pathogenicity of amyotrophic lateral sclerosis - Jessica Jeejan; Lawanya Rao; Shivank Sadasivan; Richa Lopes; Norine Dsouza (Genomics & Informatics)
Abstract Amyotrophic lateral sclerosis (ALS) is a rare neurodegenerative disease prevalent in American and European populations, with its onset and progression significantly influenced by mutations in the superoxide dismutase 1 (SOD1) protein. While previous studies have highlighted the effects of mutations in the metal-binding region and catalytic region and dimerisation of SOD1, the impact of mutations involving the Cysteine residue at the N-terminal end remains unexplored. This study investigates the effects of Cysteine-to-Trp, Phe, Ser, and Gly mutations at the 6th position of SOD1’s N-terminal end on its structural dynamics and functional impairment. Our computational analysis using PolyPhen-2, PROVEAN, Meta-SNP, and PhD-SNP predicted mutations to be deleterious, with their negative impacts likely contributing to disease development. Furthermore, stability studies and bonding pattern changes due to the mutations, analysed by mCSM, SDM, DUET, Dynamut2, and PremPS revealed changes in free energy and disruption in intramolecular interactions. The molecular dynamics studies revealed distinct changes in stability patterns among the mutations, particularly in Cys6Trp and Cys6Phe. All the mutations primarily altered the catalytic region of the protein; additionally, Cys6Phe and Cys6Gly caused disruption in the metal-binding region. The impact of mutations on the dimerisation of SOD1, analysed using MM/PBSA showed destabilisation due to Cys6Phe mutation. These findings provide molecular insights into the clinical symptoms observed in patients, highlighting the critical impact of the Cys6Phe mutation on the metal-binding and catalytic loops of SOD1 along with destabilisation of dimer formation. Overall, our analysis offers valuable insights into the molecular mechanisms driving structural changes in SOD1 due to mutations, contributing to a deeper understanding of their role in ALS pathogenicity.